PENDEKATAN SAINTIFIK DITINJAU DARI INTERAKSI GURU PADA PEMBELAJARAN DARING DI KELAS V SD NEGERI 128 PALEMBANG - Rada Cyntia Sari; Marwan Pulungan; Siti Hawa (Jurnal Inovasi Sekolah Dasar, 2021)
This study aims to describe the application of the scientific approach from teacher interactions on online learning in class V of 128 Palembang public elementary schools. This research uses a qualitative descriptive method. The results showed that, the application of the scientific approach from teacher interac tions on online based learning has been carried out but from the 5M step activities there are still some activities that have not been effective on online based learning such as teacher interactions in observing a score of 100, namely the teacher using image media and textbooks There is a score of 100 in the book and Reasoning, namely the teacher gives a task in each meeting that is categorized as very good while the Questioning activity with a score of 50 is there is no reciprocal activity between the teacher and students, Trying to score 33, the teacher only gives a few questions and communicates a score of 16, that is, the teacher does not provide opportunities for students to communicate the results of their work are categorized as Less. Based on this study, scientific-based learning improvement training is needed during the Covid-19 pandemic. Keywords: Application, scientific approach, Teacher Interactions, Online Based Learning